2015
DOI: 10.1007/s00441-015-2146-3
|View full text |Cite
|
Sign up to set email alerts
|

STED nanoscopy: a glimpse into the future

Abstract: The well-known saying of “Seeing is believing” became even more apt in biology when stimulated emission depletion (STED) nanoscopy was introduced in 1994 by the Nobel laureate S. Hell and coworkers. We presently stand at a juncture. Nanoscopy represented a revolution in fluorescence microscopy but now is a mature technique applied to many branches of biology, physics, chemistry, and materials science. We are currently looking ahead to the next generation of optical nanoscopes, to the new key player that will a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 56 publications
0
54
0
Order By: Relevance
“…Thus, the pursuit for super-resolution imaging is often accompanied by a battle for signal over noise. In the case of STED microscopy this poses specific implementation challenges (Bianchini et al, 2015), pushing continuous developments (Vicidomini et al, 2018) such as pulse synchronization and gated-detection (Leutenegger et al, 2010, Vicidomini et al, 2013, two-photon excitation Hell, 2009, Takasaki et al, 2013) or beam polarization engineering (Reuss et al, 2010, Xue et al, 2012. Here, deviating from a search for best resolution (Keller et al, 2007), it is suggested that a metric combining resolution and background noise suppression be considered, a heuristic that seems better adapted to the ampoule-shaped CH-STED PSF than the typical hourglass-shaped PSF (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the pursuit for super-resolution imaging is often accompanied by a battle for signal over noise. In the case of STED microscopy this poses specific implementation challenges (Bianchini et al, 2015), pushing continuous developments (Vicidomini et al, 2018) such as pulse synchronization and gated-detection (Leutenegger et al, 2010, Vicidomini et al, 2013, two-photon excitation Hell, 2009, Takasaki et al, 2013) or beam polarization engineering (Reuss et al, 2010, Xue et al, 2012. Here, deviating from a search for best resolution (Keller et al, 2007), it is suggested that a metric combining resolution and background noise suppression be considered, a heuristic that seems better adapted to the ampoule-shaped CH-STED PSF than the typical hourglass-shaped PSF (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Today we can say that the super-resolved fluorescence microscopy revolution lies in the fact that there is no longer any theoretical limitation to the study of the smallest details in biological cells and in any other sample. A road map and trend can be outlined as function of demand mainly comes from biology, medicine, and biophysics [61,62]. Super-resolved fluorescence methods are growing in terms Downloaded by [Rice University] at 04: of dissemination and continuing evolution [58][59][60].…”
Section: Nanoscopium Nominare Libuitmentioning
confidence: 99%
“…The first paper on super-resolution techniques is by Bianchini and colleagues (Bianchini et al, 2015) who provide an overview of the current state of the stimulated emission depletion (STED) technique. Here, the effective excitation volume is “squeezed down” from what can be achieved by lenses (“diffraction-limited”) by overlaying the spot with an equally diffraction-limited beam that switches fluorescence off.…”
Section: Overview Of the Contributions To The Special Issuementioning
confidence: 99%